Photoacoustic Flow Cytometry for Single Sickle Cell Detection In Vitro and In Vivo. (1st September 2016) - Cai, Chengzhong; Nedosekin, Dmitry A.; Menyaev, Yulian A.; Sarimollaoglu, Mustafa; Proskurnin, Mikhail A.; Zharov, Vladimir P.
Abstract : Control of sickle cell disease (SCD) stage and treatment efficiency are still time-consuming which makes well-timed prevention of SCD crisis difficult. We show here that in vivo photoacoustic (PA) flow cytometry (PAFC) has a potential for real-time monitoring of circulating sickled cells in mouse model. In vivo data were verified by in vitro PAFC and photothermal (PT) and PA spectral imaging of sickle red blood cells (sRBCs) expressing SCD-associated hemoglobin (HbS) compared to normal red blood cells (nRBCs). We discovered that PT and PA signal amplitudes from sRBCs in linear mode were 2–4-fold lower than those from nRBCs. PT and PA imaging revealed more profound spatial hemoglobin heterogeneity in sRBCs than in nRBCs, which can be associated with the presence of HbS clusters with high local absorption. This hypothesis was confirmed in nonlinear mode through nanobubble formation around overheated HbS clusters accompanied by spatially selective signal amplification. More profound differences in absorption of sRBCs than in nRBCs led to notable increase in PA signal fluctuation (fluctuation PAFC mode) as an indicator of SCD. The obtained data suggest that noninvasive label-free fluctuation PAFC has a potential for real-time enumeration of sRBCs both in vitro and in vivo .